2015
DOI: 10.1016/j.rbr.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A associação fibromialgia e lúpus eritematoso sistêmico altera a apresentação e a gravidade de ambas as doenças?

Abstract: The prevalence of FM observed in SLE patients is 12%. The presence of FM adversely affects the quality of life of patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
1
1
5
Order By: Relevance
“…The frequency of fibromyalgia in our study was lower than the 35.7% reported by Torrente-Segarra et al [44] but higher than that found by Araújo et al [45], who stated that fibromyalgia in SLE patients has a strong impact on HRQOL. Valencia-Flores et al found a rate of fibromyalgia of 9.5% in SLE patients, significantly lower than the 19.6% in patients with similar disease activity but older age and longer disease duration found in our study [37].…”
Section: Discussioncontrasting
confidence: 85%
“…The frequency of fibromyalgia in our study was lower than the 35.7% reported by Torrente-Segarra et al [44] but higher than that found by Araújo et al [45], who stated that fibromyalgia in SLE patients has a strong impact on HRQOL. Valencia-Flores et al found a rate of fibromyalgia of 9.5% in SLE patients, significantly lower than the 19.6% in patients with similar disease activity but older age and longer disease duration found in our study [37].…”
Section: Discussioncontrasting
confidence: 85%
“…El lupus eritematoso sistémico (LES) es una enfermedad autoinmune multisistémica crónica, cuya característica más llamativa, desde el punto de vista clínico y patológico, es el desarrollo de focos inflamatorios en varios tejidos y órganos del cuerpo, como por ejemplo: piel, articulaciones, riñones, vasos sanguíneos, pulmones y corazón. Se trata de una enfermedad rara que causa morbilidad y mortalidad significativas debido a su actividad inflamatoria y procesos infecciosos secundarios a la inmunosupresión inducida por la enfermedad y su tratamiento, así como las complicaciones cardiovasculares (de Araújo et al, 2015).…”
Section: Resultados Y Discusiónunclassified
“…(14) Estudo realizado em Sorocaba -SP com mulheres na faixa etária de 40 a 44 anos, divididas em três grupos (indivíduos com FM, LES e FM+ LES), identificou que a presença de FM afetava negativamente a QV de indivíduos com LES. (22) Isto também foi identificado em um relato de experiência sobre a ação da fisioterapia em indivíduos com LES, artrite reumatoide e FM (23) e no presente estudo, visto ter sido identificado que indivíduos com FM apresentaram maiores chances de insatisfação nos domínios saúde física, psicológica e meio ambiente. Ressalta-se ainda que a prevalência de FM foi de 12,06%, discretamente menor que o encontrado na literatura, que aponta variação de 17% a 22%.…”
Section: Discussionunclassified